Cytoprotective Co-chaperone BcBAG1 Is a Component for Fungal Development, Virulence, and Unfolded Protein Response (UPR) of Botrytis cinerea - Zhang, Honghong; Li, Yurong; Dickman, Martin B.; Wang, Zonghua (Frontiers in Microbiology, 2019)
The Bcl-2 associated athanogene (BAG) family is an evolutionarily conserved group of co-chaperones that confers stress protection against a variety of cellular insults extending from yeasts, plants to humans. Little is known, however, regarding the biological role of BAG proteins in phytopathogenic fungi. Here, we identified the unique BAG gene (BcBAG1) from the necrotrophic fungal pathogen, Botrytis cinerea. BcBAG1 is the homolog of Arabidopsis thaliana AtBAG4, and ectopic expression of BcBAG1 in atbag4 knock-out mutants restores salt tolerance. BcBAG1 deletion mutants (ΔBcbag1) exhibited decreased conidiation, enhanced melanin accumulation and lost the ability to develop sclerotia. Also, BcBAG1 disruption blocked fungal conidial germination and successful penetration, leading to a reduced virulence in host plants. BcBAG1 contains BAG (BD) domain at C-terminus and ubiquitin-like (UBL) domain at N-terminus. Complementation assays indicated that BD can largely restored pathogenicity of ΔBcbag1. Abiotic stress assays showed ΔBcbag1 was more sensitive than the wild-type strain to NaCl, Calcoflour white, SDS, tunicamycin, DTT, heat and cold stress, suggesting BcBAG1 plays a cytoprotective role during salt stress, cell wall stress and ER stress. BcBAG1 negatively regulated the expression of BcBIP1, BcIRE1 and the splicing of BcHAC1 mRNA, which are core regulators of unfolded protein response (UPR) during ER stress. Moreover, BcBAG1 interacted with HSP70-type chaperones, BcBIP1 and BcSKS2. In summary, this work demonstrates that BcBAG1 is pleiotropic and not only essential for fungal development, hyphal melanization and virulence, but also required for response to multiple abiotic stresses and UPR pathway of B. cinerea.